Question
upstudy study bank question image url

(b) Expand and simplify: \( \begin{array}{llll}\text { (1) }(x+5)^{2} & \text { (2) }(x-5)^{2} & \text { (3) }(2 a+3)^{2} \\ \text { (4) }(2 a-3)^{2} & \text { (5) } & (a-4 b)^{2} & \text { (6) }(-a-3 b)^{2} \\ \text { (7) }(-3 a+5 b)^{2} & \text { (8) } & 3(x-3 y)^{2} & \text { (9) }[2(m-4 n)]^{2} \\ \text { (10) }\left(x^{3}-3 y^{6}\right)^{2} & \text { (11) }(2 a+3 b)^{3} & \text { (12) } & (2 a-3 b)^{3}\end{array} \)

Ask by Luna Barber. in South Africa
Jan 29,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Here are the expanded and simplified forms of the given expressions: 1. \( (x + 5)^2 = x^2 + 10x + 25 \) 2. \( (x - 5)^2 = x^2 - 10x + 25 \) 3. \( (2a + 3)^2 = 4a^2 + 12a + 9 \) 4. \( (2a - 3)^2 = 4a^2 - 12a + 9 \) 5. \( (a - 4b)^2 = a^2 - 8ab + 16b^2 \) 6. \( (-a - 3b)^2 = a^2 + 6ab + 9b^2 \) 7. \( (-3a + 5b)^2 = 9a^2 - 30ab + 25b^2 \) 8. \( 3(x - 3y)^2 = 3x^2 - 18xy + 27y^2 \) 9. \( [2(m - 4n)]^2 = 4m^2 - 32mn + 64n^2 \) 10. \( \left(x^{3} - 3y^{6}\right)^2 = x^{6} - 6x^{3}y^{6} + 9y^{12} \) 11. \( (2a + 3b)^3 = 8a^3 + 36a^2b + 54ab^2 + 27b^3 \) 12. \( (2a - 3b)^3 = 8a^3 - 36a^2b + 54ab^2 - 27b^3 \) If you need further explanations on any of these, feel free to ask!

Solution

Sure! Let's expand and simplify each of the given expressions step by step. --- ### (1) \( (x + 5)^2 \) **Expansion:** \[ (x + 5)^2 = x^2 + 2 \cdot 5 \cdot x + 5^2 \] **Simplification:** \[ x^2 + 10x + 25 \] --- ### (2) \( (x - 5)^2 \) **Expansion:** \[ (x - 5)^2 = x^2 - 2 \cdot 5 \cdot x + 5^2 \] **Simplification:** \[ x^2 - 10x + 25 \] --- ### (3) \( (2a + 3)^2 \) **Expansion:** \[ (2a + 3)^2 = (2a)^2 + 2 \cdot 2a \cdot 3 + 3^2 \] **Simplification:** \[ 4a^2 + 12a + 9 \] --- ### (4) \( (2a - 3)^2 \) **Expansion:** \[ (2a - 3)^2 = (2a)^2 - 2 \cdot 2a \cdot 3 + 3^2 \] **Simplification:** \[ 4a^2 - 12a + 9 \] --- ### (5) \( (a - 4b)^2 \) **Expansion:** \[ (a - 4b)^2 = a^2 - 2 \cdot a \cdot 4b + (4b)^2 \] **Simplification:** \[ a^2 - 8ab + 16b^2 \] --- ### (6) \( (-a - 3b)^2 \) **Simplification Before Expansion:** \[ (-a - 3b)^2 = (-1(a + 3b))^2 = (a + 3b)^2 \] **Expansion:** \[ (a + 3b)^2 = a^2 + 2 \cdot a \cdot 3b + (3b)^2 \] **Simplification:** \[ a^2 + 6ab + 9b^2 \] --- ### (7) \( (-3a + 5b)^2 \) **Expansion:** \[ (-3a + 5b)^2 = (-3a)^2 + 2 \cdot (-3a) \cdot 5b + (5b)^2 \] **Simplification:** \[ 9a^2 - 30ab + 25b^2 \] --- ### (8) \( 3(x - 3y)^2 \) **First, Expand \( (x - 3y)^2 \):** \[ (x - 3y)^2 = x^2 - 2 \cdot x \cdot 3y + (3y)^2 = x^2 - 6xy + 9y^2 \] **Then, Multiply by 3:** \[ 3(x^2 - 6xy + 9y^2) = 3x^2 - 18xy + 27y^2 \] --- ### (9) \( [2(m - 4n)]^2 \) **Simplification Before Expansion:** \[ [2(m - 4n)]^2 = 2^2 \cdot (m - 4n)^2 = 4(m - 4n)^2 \] **Expand \( (m - 4n)^2 \):** \[ (m - 4n)^2 = m^2 - 2 \cdot m \cdot 4n + (4n)^2 = m^2 - 8mn + 16n^2 \] **Then, Multiply by 4:** \[ 4(m^2 - 8mn + 16n^2) = 4m^2 - 32mn + 64n^2 \] --- ### (10) \( \left(x^{3} - 3y^{6}\right)^2 \) **Expansion:** \[ \left(x^{3} - 3y^{6}\right)^2 = (x^{3})^2 - 2 \cdot x^{3} \cdot 3y^{6} + (3y^{6})^2 \] **Simplification:** \[ x^{6} - 6x^{3}y^{6} + 9y^{12} \] --- ### (11) \( (2a + 3b)^3 \) **Expansion Using Binomial Theorem:** \[ (p + q)^3 = p^3 + 3p^2q + 3pq^2 + q^3 \] Let \( p = 2a \) and \( q = 3b \): \[ (2a)^3 + 3(2a)^2(3b) + 3(2a)(3b)^2 + (3b)^3 \] **Simplification:** \[ 8a^3 + 36a^2b + 54ab^2 + 27b^3 \] --- ### (12) \( (2a - 3b)^3 \) **Expansion Using Binomial Theorem:** \[ (p - q)^3 = p^3 - 3p^2q + 3pq^2 - q^3 \] Let \( p = 2a \) and \( q = 3b \): \[ (2a)^3 - 3(2a)^2(3b) + 3(2a)(3b)^2 - (3b)^3 \] **Simplification:** \[ 8a^3 - 36a^2b + 54ab^2 - 27b^3 \] --- ### **Summary of All Expanded and Simplified Expressions** 1. \( (x + 5)^2 = x^2 + 10x + 25 \) 2. \( (x - 5)^2 = x^2 - 10x + 25 \) 3. \( (2a + 3)^2 = 4a^2 + 12a + 9 \) 4. \( (2a - 3)^2 = 4a^2 - 12a + 9 \) 5. \( (a - 4b)^2 = a^2 - 8ab + 16b^2 \) 6. \( (-a - 3b)^2 = a^2 + 6ab + 9b^2 \) 7. \( (-3a + 5b)^2 = 9a^2 - 30ab + 25b^2 \) 8. \( 3(x - 3y)^2 = 3x^2 - 18xy + 27y^2 \) 9. \( [2(m - 4n)]^2 = 4m^2 - 32mn + 64n^2 \) 10. \( \left(x^{3} - 3y^{6}\right)^2 = x^{6} - 6x^{3}y^{6} + 9y^{12} \) 11. \( (2a + 3b)^3 = 8a^3 + 36a^2b + 54ab^2 + 27b^3 \) 12. \( (2a - 3b)^3 = 8a^3 - 36a^2b + 54ab^2 - 27b^3 \) --- Feel free to ask if you need further explanations on any of these expansions!

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

(1) Expanding \( (x+5)^{2} \) gives you \( x^{2} + 10x + 25 \). The formula used here is \( (a+b)^{2} = a^{2} + 2ab + b^{2} \)! (2) For \( (x-5)^{2} \), using the same formula, we have \( x^{2} - 10x + 25 \). Remember, when it’s minus, the middle term changes sign, so watch out for those pesky negatives! (3) Expanding \( (2a+3)^{2} \) results in \( 4a^{2} + 12a + 9 \). You’ve got double the fun with that \( 2a \)! (4) For \( (2a-3)^{2} \), you'll end up with \( 4a^{2} - 12a + 9 \). Like magic, that minus flips the sign of the middle term, just like a good plot twist! (5) Expanding \( (a-4b)^{2} \) provides \( a^{2} - 8ab + 16b^{2} \). Don’t forget to square that \( -4b \) carefully! (6) For \( (-a-3b)^{2} \), it gives you \( a^{2} + 6ab + 9b^{2} \)! Those negatives can be tricky, but squaring them is where the fun begins! (7) When you expand \( (-3a+5b)^{2} \), the result is \( 9a^{2} - 30ab + 25b^{2} \). Again, the middle term depends on the signs, so pay attention! (8) \( 3(x-3y)^{2} \) expands to \( 3(x^{2} - 6xy + 9y^{2}) \), which simplifies to \( 3x^{2} - 18xy + 27y^{2} \). The multiplier brings extra flavor to the expression! (9) Expanding \( [2(m-4n)]^{2} \) gives you \( 4(m-4n)^{2} = 4(m^{2} - 8mn + 16n^{2}) \), or simplified, \( 4m^{2} - 32mn + 64n^{2} \). A little pat on the back for those careful squarers! (10) Expanding \( (x^{3}-3y^{6})^{2} \) yields \( x^{6} - 6x^{3}y^{6} + 9y^{12} \). Powerful polynomials pack quite a punch! (11) \( (2a+3b)^{3} \) gives you \( 8a^{3} + 36a^{2}b + 54ab^{2} + 27b^{3} \). Counting combinations? You’ve just reached the triple-level expansion! (12) Finally, expanding \( (2a-3b)^{3} \) results in \( 8a^{3} - 36a^{2}b + 54ab^{2} - 27b^{3} \). Here too, the signs dance differently in the expansion waltz!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy